Evaluasi Sistem Operasional dan Pemeliharaan Jaringan Irigasi pada Sistem Subak di Kawasan Warisan Budaya Dunia Catur Angga Batukau - Ni Made Ayu Adi Suartiani; Sumiyati Sumiyati; I Wayan Tika (Jurnal BETA (Biosistem dan Teknik Pertanian), 2017)
Subak is a traditional irrigation organization in Bali, one of whose functions is to manage irrigation. Operation and maintenance (O&P) of irrigation networks is an activity involving monitoring and cleaning irrigation networks in subak. The purpose of this research was to determine the physical performance of irrigation networks and the operation and maintenance (O&M) system of irrigation networks at three subak sites located in Catur Angga Batukau, one of the World Cultural Heritage sites. The methods used in this research were survey and observation methods. The collected data were assigned weighted values and analyzed. Subak was assessed using three criteria, namely Good = 3, Medium = 2, and Less = 1. System analysis was conducted using a fuzzy logic approach. The results of the analysis indicated that the performance of the irrigation network at Subak Jatiluwih was 2.49 (medium), Subak Tengkudak was 2.42 (medium), and Subak Rejasa was 2.50 (medium). From the three subak sites, the results showed that subaks in Catur Angga Batukau were in medium condition; therefore, there is a need to increase maintenance of the irrigation networks.